2012
DOI: 10.1007/s00464-012-2295-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional vision enhances task performance independently of the surgical method

Abstract: The more complex the task, the more 3D vision accelerates task completion compared with 2D vision. The gain in task performance is independent of the surgical method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 38 publications
2
88
1
6
Order By: Relevance
“…Thus, more recent studies have suggested a possible advantage provided by these new 3D systems during laparoscopic performance. [3][4][5] However, comparative assessments of new generation 3D vs 2D laparoscopy remain limited, especially in the urology field.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, more recent studies have suggested a possible advantage provided by these new 3D systems during laparoscopic performance. [3][4][5] However, comparative assessments of new generation 3D vs 2D laparoscopy remain limited, especially in the urology field.…”
Section: Resultsmentioning
confidence: 99%
“…During the SILS, frequent movement of camera scope is more limited compared to conventional multiport laparoscopic surgery because of collision of instruments. Recently developed 3D scope system could be useful in terms of superior task efficiency because it can show more effective perspective and depth of field to operator, which means the decreased number of "air-catching" and less position change of camera scope (29)(30)(31). Secondly, the length and shape of instrument can be chosen depending on the situation.…”
Section: Prerequisitesmentioning
confidence: 99%
“…Various reports in the existing literature have already shown that stereoscopic vision decreases surgery time and increases accuracy for the surgeon behind the console of the Da Vinci robot. [3][4][5][6][7][8][9][10] However, to the best of our knowledge to date, there is little or no published evidence illustrating the impact of using a 3-D auxiliary monitor for the assistant(s) at the operating table during robot-assisted laparoscopy (RAL). For the assistant(s), these facilities are not currently widely available, although it seems some 3-D auxiliary monitor systems are beginning to emerge on the market.…”
Section: Introductionmentioning
confidence: 99%